Corporate Finance and Credit Constraints in a Transitional Economy: Insights from Borrowers’ Relations in Mongolia - Takaharu Ishii (International Journal of Regional Development, 2022)
This study examines changes in the extent of access to finance in order to ascertain how states that have transitioned from socialist to capitalist regimes have deepened their capitalist systems. To understand the extent of capitalization, it is important to confirm whether there are widespread opportunities for income growth in the country through structural reforms and economic growth since democratization, as access to finance as a safety net for the vulnerable has expanded, especially for the poor, especially in micro-enterprises where many of the poor are employed. This study focuses on micro-enterprises in Mongolia and examines changes over the last 20-25 years since capitalization. The first half of the paper deals with the financing situation of microenterprises, while the second half examines whether microenterprises are experiencing credit constraints through regression analysis. The data were collected by the author in 2011 and 2017, mainly in Ulaanbaatar, the capital of Mongolia.